The Evolution of Restorative Justice in the National Criminal Justice System - Zubedi, Zulfikar; Aji Prasetyo, Achmad (Universitas Negeri Gorontalo, 2025)
The transformation of law enforcement in Indonesia is an effort to create a fair and effective legal system, but the journey towards it is faced with major challenges between ideal expectations and existing realities. Although various reforms of law enforcement institutions and the application of technology in the legal process have been carried out, inequality in access to justice, political intervention, and low integrity of officers are still significant problems. This article aims to analyze the dynamics of law enforcement transformation in Indonesia by looking at the gap between public expectations of the supremacy of law and the reality that occurs in the field, as well as identifying inhibiting and driving factors in realizing effective and just law enforcement. Based on a juridical-sociological approach, this study critiques developments and provides recommendations for strengthening legal institutions in order to realize a better legal system in Indonesia.